Lilac time - Michaels, Fern; Foster, Lori, 1958-; Brown, Carolyn, 1948- (Kensington Publishing Corp., 2025)
Sweet as Honey: "Natalie is through with pining over her ex. If only her efforts to be social again didn't lead to repeated run-ins with an infuriating beekeeper at the local farmer's market. Yet Garrett keeps buzzing around. And as Natalie watches his patience and dedication in tending his hives, she begins to wonder if life has a sweet surprise in store." --